Apply the Zero Power Rule of Integer Exponents to solve 2.3+(−1.478)0.(1 point)
2.3+(−1.478)0=
24 answers
2.3 + (-1.478)^0 = 2.3 + 1 = 3.3
Apply the Zero Power Rule of Integer Exponents to solve −40⋅15.(1 point)
−40⋅15=
−40⋅15=
-40⋅15 = -600
Apply the Zero Power Rule of Integer Exponents to solve −40⋅15.(1 point)
−40⋅15=
−40⋅15=
The zero power rule states that any non-zero number raised to the power of zero is equal to 1. However, in this case, we are not dealing with exponents, but rather multiplication. Therefore, we can simply multiply -40 by 15.
-40 * 15 = -600
-40 * 15 = -600
whats the answer?
The answer is -600.
wrong
Apologies for the confusion. The answer to -40 * 15 is -600.
Apply the Zero Power Rule to create an equivalent expression to 43(−2+10).(1 point)
An equivalent expression to 43(−2+10) is 43(−2+
).
An equivalent expression to 43(−2+10) is 43(−2+
).
An equivalent expression to 43(−2+10) is 43(−2+0) since any number raised to the power of 0 is equal to 1.
Solve the expression 2(1.60+7)−4.90.(1 point)
2(1.60+7)−4.90=
.
2(1.60+7)−4.90=
.
To solve the expression 2(1.60+7)−4.90, we first simplify the parentheses by adding 1.60 and 7:
1.60 + 7 = 8.60
Next, we multiply 2 by the result:
2 * 8.60 = 17.20
Finally, we subtract 4.90 from the result:
17.20 - 4.90 = 12.30
Therefore, 2(1.60+7)−4.90 = 12.30.
1.60 + 7 = 8.60
Next, we multiply 2 by the result:
2 * 8.60 = 17.20
Finally, we subtract 4.90 from the result:
17.20 - 4.90 = 12.30
Therefore, 2(1.60+7)−4.90 = 12.30.
Which of the following is developed to result in the answer of 1?(1 point)
Responses
13−(7.42)0
13 minus left parenthesis 7.42 right parenthesis superscript 0 baseline
3(80)
3 left parenthesis 8 superscript 0 baseline right parenthesis
(−2.97)0
left parenthesis negative 2.97 right parenthesis superscript 0 baseline
50+90
Responses
13−(7.42)0
13 minus left parenthesis 7.42 right parenthesis superscript 0 baseline
3(80)
3 left parenthesis 8 superscript 0 baseline right parenthesis
(−2.97)0
left parenthesis negative 2.97 right parenthesis superscript 0 baseline
50+90
The expression that is developed to result in the answer of 1 is (−2.97)^0. Any non-zero number raised to the power of zero is equal to 1 according to the Zero Power Rule of Integer Exponents.
Which of the following shows the correct process of solving −30+4.5?(1 point)
Responses
−30+4.5=−3⋅0+4.5=0+4.5=4.5
negative 3 superscript 0 baseline plus 4.5 equals negative 3 times 0 plus 4.5 equals 0 plus 4.5 equals 4.5
−30+4.5=−3+4.5=1.5
negative 3 superscript 0 baseline plus 4.5 equals negative 3 plus 4.5 equals 1.5
−30+4.5=(−3)0+4.5=1+4.5=5.5
negative 3 superscript 0 baseline plus 4.5 equals left parenthesis negative 3 right parenthesis superscript 0 baseline plus 4.5 equals 1 plus 4.5 equals 5.5
−30+4.5=−1⋅30+4.5=−1⋅1+4.5=−1+4.5=3.5
negative 3 superscript 0 baseline plus 4.5 equals negative 1 times 3 superscript 0 baseline plus 4.5 equals negative 1 dot 1 plus 4.5 equals negative 1 plus 4.5 equals 3.5
Responses
−30+4.5=−3⋅0+4.5=0+4.5=4.5
negative 3 superscript 0 baseline plus 4.5 equals negative 3 times 0 plus 4.5 equals 0 plus 4.5 equals 4.5
−30+4.5=−3+4.5=1.5
negative 3 superscript 0 baseline plus 4.5 equals negative 3 plus 4.5 equals 1.5
−30+4.5=(−3)0+4.5=1+4.5=5.5
negative 3 superscript 0 baseline plus 4.5 equals left parenthesis negative 3 right parenthesis superscript 0 baseline plus 4.5 equals 1 plus 4.5 equals 5.5
−30+4.5=−1⋅30+4.5=−1⋅1+4.5=−1+4.5=3.5
negative 3 superscript 0 baseline plus 4.5 equals negative 1 times 3 superscript 0 baseline plus 4.5 equals negative 1 dot 1 plus 4.5 equals negative 1 plus 4.5 equals 3.5
The correct process of solving −30+4.5 is as follows:
−30+4.5=−3⋅0+4.5=0+4.5=4.5
Therefore, the correct response is:
−30+4.5=−3⋅0+4.5=0+4.5=4.5
−30+4.5=−3⋅0+4.5=0+4.5=4.5
Therefore, the correct response is:
−30+4.5=−3⋅0+4.5=0+4.5=4.5
Which of the following is an equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule? (1 point)
Responses
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.3+4⋅9
Start Fraction 7 over 5.3 End Fraction plus 4 times 9
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
75.30+36
Responses
71+4⋅9
Start Fraction 7 over 1 End Fraction plus 4 times 9
75.3+4⋅9
Start Fraction 7 over 5.3 End Fraction plus 4 times 9
70+4⋅9
Start Fraction 7 over 0 End Fraction plus 4 times 9
75.30+36
The equivalent expression to 7(-5.3)^0+4*9 when applying the Zero Power Rule is 71+4*9.
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)
Responses
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(2)+1
Responses
12(9−1)+1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis plus 1
12(9−1)−1
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 1 right parenthesis minus 1
12(9−0)+0
Start Fraction 1 over 2 End Fraction left parenthesis 9 minus 0 right parenthesis plus 0
12(2)+1
The equivalent expression to 12(9-70)+(-29)^0 is 12(9-0)+0.
Which of the following shows the correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule? (1 point)
Responses
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 4 times 5 equals negative 20
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 16 plus 1 equals negative 15
−4(3+120)+150=−4(15)+1=−60+1=−59
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 1 equals negative 60 plus 1 equals negative 59
−4(3+120)+150 =−4(15)+15=−60+15=−45
Responses
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−4⋅5=−20
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 4 times 5 equals negative 20
−4(3+120)+150=−4(3+1)+1=−4⋅4+1=−16+1=−15
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 3 plus 1 right parenthesis plus 1 equals negative 4 times 4 plus 1 equals negative 16 plus 1 equals negative 15
−4(3+120)+150=−4(15)+1=−60+1=−59
negative 4 left parenthesis 3 plus 12 superscript 0 baseline right parenthesis plus 15 superscript 0 baseline equals negative 4 left parenthesis 15 right parenthesis plus 1 equals negative 60 plus 1 equals negative 59
−4(3+120)+150 =−4(15)+15=−60+15=−45
The correct process of solving −4(3+120)+150 by generating an equivalent expression using the Zero Power Rule is:
−4(3+120)+150 = −4(15)+150 = −60 + 150 = 90
Therefore, none of the provided responses show the correct process. The correct answer is −4(3+120)+150 = 90.
−4(3+120)+150 = −4(15)+150 = −60 + 150 = 90
Therefore, none of the provided responses show the correct process. The correct answer is −4(3+120)+150 = 90.
still wrong it isnt -600 or 600 do the right answer